Heart Weight Is an Independent Factor Associated With, But Is a Poor Predictor for, Sudden Cardiac Death. (6th March 2022) - Garland, Jack; Kesha, Kilak; Glenn, Charley; Stables, Simon; Ondruschka, Benjamin; Lohner, Larissa; Tse, Rexson
Abstract: An enlarged heart can cause electrical instability and impaired contractility, leading to fatal arrhythmia and acute heart failure, and is associated with sudden cardiac death. However, there is limited postmortem evidence on whether heart weight is an independent factor associated with sudden cardiac death. This 18-month retrospective study examined 108 adult heart weights in which all the hearts were weighed after dissection, blood and blood clots removed, rinsed in water, and pat dried. The multivariate logistic regression analysis showed heart weight was an independent factor associated with sudden cardiac death. However, after normalization, the heart weight was a poor predictor of sudden cardiac death with an area under the curve less than 0.7 in the plotted receiver operating characteristic curve.